Antibacterial and antioxidant composite hydrogel as well as preparation method and application thereof

Through zinc ions-loaded lithostone, gallic acid-grafted methacrylated gelatin and arginine-grafted methacrylated chitosan composite hydrogel, wound dressings in the prior art are solved by the composite hydrogel of wound dressings in the prior art. The problem of poor effect of oxycillin Staphylococcus aureus infection has achieved effective antibacterial and antioxidant properties, promoting wound healing and reducing inflammatory responses.

CN119113193APending Publication Date: 2024-12-13WUHAN UNIV OF TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411176808.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing wound dressings are not effective in treating methicillin-resistant Staphylococcus aureus infection, and long-term use can easily lead to the development of bacterial resistance, making it difficult to ensure rapid and healthy healing of wounds.

Method used

Antibacterial and antioxidant composite hydrogel formed by interpenetrating cross-linking of zinc ions-loaded lithosite, gallic acid-grafted methacrylated gelatin and arginine-grafted methacrylated chitosan, through light The initiator undergoes cross-linking reaction under ultraviolet light to prepare a hydrogel with antibacterial and antioxidant properties.

Benefits of technology

The prepared hydrogel has good antibacterial properties and can effectively kill MRSA bacteria, promote wound healing, reduce inflammatory response, and show good biocompatibility and hemocompatibility, reducing damage to cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113193A_ABST
    Figure CN119113193A_ABST
Patent Text Reader

Abstract

The invention discloses antibacterial and antioxidant composite hydrogel as well as a preparation method and application thereof. The antibacterial and antioxidant composite hydrogel is hydrogel formed by interpenetrating and cross-linking zinc ion loaded hectorite, gallic acid grafted methacrylated gelatin and arginine grafted methacrylated chitosan, the preparation method comprises the following steps: by taking gelatin and chitosan with good biocompatibility as substrate materials, carrying out grafting modification to obtain gallic acid-methacrylated gelatin (gallic acid grafted methacrylated gelatin) and arginine-methacrylated chitosan (arginine grafted methacrylated chitosan); the preparation method comprises the following steps: firstly, preparing a hydrogel, then mixing the hydrogel with zinc-hectorite (hectorite loaded with zinc ions) to prepare a stock solution, carrying out photo-crosslinking to form the hydrogel, and the prepared hydrogel has good antibacterial property, oxidation resistance, biocompatibility and blood compatibility, and can promote cell growth and wound healing and reduce inflammatory response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to an antibacterial and antioxidant composite hydrogel and a preparation method and application thereof. Background Art

[0002] As a communication medium between the human microenvironment and the external environment, the skin plays an important role in metabolic regulation and information exchange. As an important interface between the body and the surrounding environment, a variety of microbial communities coexist, including bacteria, fungi and viruses. In particular, different microbial communities have a significant impact on local and systemic immune responses. Chronic wounds caused by bacterial infections have become a major medical threat and challenge, as bacteria can compete with the immune system and subsequently invade living tissues, often resulting in severe tissue damage. The use of antibiotics has led to the emergence of drug-resistant bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA), which seriously affects wound healing and has a huge impact on patients and the socio-economics. Wound dressings play a vital role in the management of skin wounds, as they protect wounds and promote the regeneration of skin and epidermal tissues.

[0003] However, there is a practical problem in clinical practice. Methicillin-resistant Staphylococcus aureus wound infections still rely more on drug treatment, which may cause more bacterial resistance and poor treatment effect. For a long time, the development of multifunctional and high-performance materials for the treatment of wound infections has been urgent.

[0004] Therefore, in order to ensure rapid and healthy wound healing, wound anti-infection and post-injury treatment of biomaterial dressings are particularly important. Summary of the invention

[0005] In view of this, the present application provides an antibacterial and antioxidant composite hydrogel and a preparation method and application thereof, which are used to solve the problem of how to improve the antibacterial and antioxidant properties of hydrogel as a medical dressing.

[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides an antibacterial and antioxidant composite hydrogel, which is a hydrogel formed by interpenetrating and cross-linking of zinc ion-loaded laponite, gallic acid-grafted methacryloyl gelatin, and arginine-grafted methacryloyl chitosan.

[0007] In a second aspect, the present application provides a method for preparing an antibacterial and antioxidant composite hydrogel, comprising the following steps: S1. Using laponite and zinc nitrate as raw materials, a loading reaction is carried out, and after centrifugation, laponite loaded with zinc ions is obtained; using methacrylic anhydride and gallic acid as raw materials, gelatin is modified to obtain gallic acid-grafted methacrylylated gelatin; using methacrylic anhydride and arginine as raw materials, chitosan is modified to obtain arginine-grafted methacrylylated chitosan; S2. In the dispersion of the photoinitiator, zinc ion-loaded laponite, gallic acid-grafted methacryloyl gelatin, and arginine-grafted methacryloyl chitosan are added in a dark place, stirred evenly, and then cross-linked under ultraviolet light to obtain an antibacterial and antioxidant composite hydrogel.

[0008] Preferably, the mass ratio of zinc ion-loaded laponite, gallic acid-grafted methacryloyl gelatin, and arginine-grafted methacryloyl chitosan is (0.1-0.5): (0.2-2): (10-30).

[0009] Preferably, in step S1, the preparation process of the zinc ion-loaded hectorite is: adding the hectorite to water and stirring to swell, then adding zinc nitrate and stirring to carry out a loading reaction, and then centrifuging, washing, and drying to obtain the zinc ion-loaded hectorite.

[0010] Preferably, in step S1, the preparation process of gallic acid grafted methacryloyl gelatin is: mixing a PBS solution of gelatin with methacrylic anhydride, heating for reaction, dialyzing, and freeze-drying to obtain methacryloyl gelatin; adding gallic acid, EDC, and NHS to a PBS solution of methacryloyl gelatin, performing a coupling reaction, and then dialyzing and freeze-drying to obtain gallic acid grafted methacryloyl gelatin.

[0011] Preferably, the temperature of the heating reaction is 50-55° C., and the time of the heating reaction is 3-5 h; the temperature of the coupling reaction is 25-40° C., and the time of the coupling reaction is 24-36 h.

[0012] Preferably, in step S1, the preparation process of arginine grafted methacrylylated chitosan is: chitosan, acetic acid, and PBS are mixed and stirred to obtain a chitosan solution; methacrylic anhydride is added to the chitosan solution, heated for reaction, dialyzed, and freeze-dried to obtain methacrylylated chitosan; arginine, EDC, and NHS are added to the PBS solution of methacrylylated chitosan, and a coupling reaction is carried out, and dialyzed and freeze-dried to obtain arginine grafted methacrylylated chitosan.

[0013] Preferably, the temperature of the heating reaction is 30-40°C, and the heating reaction time is 3-4h; the temperature of the coupling reaction is 25-40°C, and the coupling reaction time is 24-36h.

[0014] Preferably, the photoinitiator comprises photoinitiator 12959.

[0015] In a third aspect, the present application provides an application of an antibacterial and antioxidant composite hydrogel in the preparation of medical wound repair materials.

[0016] The beneficial effects of the present application are as follows: the present invention uses gelatin and chitosan with good biocompatibility as base materials, which are modified by grafting into gallic acid-methacryloyl gelatin (gallic acid grafted methacryloyl gelatin) and arginine-methacryloyl chitosan (arginine grafted methacryloyl chitosan), and then mixed with zinc-lithium laponite (lithium laponite loaded with zinc ions) to prepare a stock solution, which is photocrosslinked to form a hydrogel. The prepared hydrogel has good antibacterial, antioxidant, biocompatibility and blood compatibility, and can promote blast growth, wound healing and reduce inflammatory response. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The cytotoxicity test results of different composite hydrogels; Figure 2 The experimental results of antioxidant properties of different composite hydrogels. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0019] The present application provides an antibacterial and antioxidant composite hydrogel, which is a hydrogel formed by interpenetrating and cross-linking of zinc ion-loaded laponite, gallic acid-grafted methacryloyl gelatin, and arginine-grafted methacryloyl chitosan.

[0020] The present application provides a method for preparing an antibacterial and antioxidant composite hydrogel, comprising the following steps: S1. Using laponite and zinc nitrate as raw materials, a loading reaction is carried out, and after centrifugation, laponite loaded with zinc ions is obtained; using methacrylic anhydride and gallic acid as raw materials, gelatin is modified to obtain gallic acid-grafted methacrylylated gelatin; using methacrylic anhydride and arginine as raw materials, chitosan is modified to obtain arginine-grafted methacrylylated chitosan; S2. In the dispersion of the photoinitiator, zinc ion-loaded laponite, gallic acid-grafted methacryloyl gelatin, and arginine-grafted methacryloyl chitosan are added in a dark place, stirred evenly, and then cross-linked under ultraviolet light to obtain an antibacterial and antioxidant composite hydrogel.

[0021] The invention uses chitosan and gelatin with good biocompatibility as base materials, modifies chitosan and gelatin to obtain arginine-methacrylylated chitosan and gallic acid-methacrylylated gelatin, then dopes them with zinc-hectorite nanoparticles and prepare composite hydrogel through photo-crosslinking. The prepared composite hydrogel has good antibacterial property and biocompatibility, can kill MRSA bacteria, promote angiogenesis, wound healing and reduce inflammatory response.

[0022] In this application, gallic acid-methacryloyl gelatin (GA-GelMA) is a double-bond modified gelatin that can be cross-linked and cured into gel under the action of ultraviolet and visible light in the presence of a photoinitiator. GA-GelMA has the characteristics of both natural and synthetic biomaterials, with a three-dimensional structure suitable for cell growth and differentiation, excellent biocompatibility and cell response properties, and can replace artificial basement membranes or other natural collagen hydrogels. In addition, GelMA has good thermosensitive gel properties, biocompatibility and degradability, and its mechanical properties are adjustable, which can regulate cell adhesion, promote wound healing and vascularization.

[0023] In some embodiments, the mass ratio of zinc ion-loaded laponite, gallic acid-grafted methacryloyl gelatin, and arginine-grafted methacryloyl chitosan is (0.1-0.5): (0.2-2): (10-30).

[0024] Specifically, in the antibacterial and antioxidant composite hydrogel, the content of zinc-lithium laponite is 0.1~0.5wt%; the content of arginine-methacryloyl chitosan is 0.2~2wt%; the content of gallic acid-methacryloyl gelatin is 10~30wt%; and the content of photoinitiator I2959 is 0.5~2wt%.

[0025] In some embodiments, in step S1, the preparation process of zinc ion loaded hectorite is: adding hectorite to water and stirring to swell, then adding zinc nitrate and stirring to carry out loading reaction, and then centrifuging, washing, and drying to obtain zinc ion loaded hectorite.

[0026] Specifically, in step S1, the preparation process of zinc ion-loaded hectorite is as follows: adding 5-50 mg / mL of hectorite to water and stirring for swelling, the stirring and swelling time is 30-60 min, and then adding zinc nitrate and stirring for 12-24 h to load the drug, and after loading, centrifuging at 6000-9000 r / min for 5-10 min to obtain a solid, and then washing the solid multiple times with water whose volume is 1-5 times that of the material after centrifugation, and then freeze-drying to obtain zinc ion-loaded hectorite.

[0027] In some embodiments, in step S1, the preparation process of gallic acid grafted methacryloyl gelatin is: mixing a PBS solution of gelatin with methacrylic anhydride, heating for reaction, dialyzing, and freeze-drying to obtain methacryloyl gelatin; adding gallic acid, EDC, and NHS to a PBS solution of methacryloyl gelatin, performing a coupling reaction, and then dialyzing and freeze-drying to obtain gallic acid grafted methacryloyl gelatin.

[0028] In some embodiments, the temperature of the heating reaction is 50-55°C, and the heating reaction time is 3-5 hours; the temperature of the coupling reaction is 25-40°C, and the coupling reaction time is 24-36 hours.

[0029] Specifically, in step S1, the preparation process of gallic acid grafted methacrylic acid gelatin is as follows: gelatin and PBS buffer solution are dissolved at a mass ratio of 0.02-0.1:1 at 55-60°C for 30-90 minutes; methacrylic anhydride and the prepared solution are added to the solution at a volume ratio of 0.1-0.2:1, reacted at 50-55°C for 3-5 hours, dialyzed, freeze-dried, to obtain methacrylic acid gelatin; the obtained methacrylic acid gelatin and P BS buffer is dissolved at a mass ratio of 0.01-0.02:1 at 40-50°C for 30-90 min; gallic acid, EDC, NHS and the prepared solution are added to the solution at a mass ratio of 0.01-0.05:0.01-0.05:0.005-0.025:1, reacted at 25-40°C for 24 h, dialyzed and freeze-dried to obtain gallic acid-grafted methacryloyl gelatin (gallic acid-methacryloyl gelatin).

[0030] In some embodiments, in step S1, the preparation process of arginine grafted methacryloyl chitosan is: chitosan, acetic acid, and PBS are mixed and stirred to obtain a chitosan solution; methacrylic anhydride is added to the chitosan solution, heated for reaction, dialyzed, and freeze-dried to obtain methacryloyl chitosan; arginine, EDC, and NHS are added to the PBS solution of methacryloyl chitosan, a coupling reaction is carried out, and dialyzed and freeze-dried to obtain arginine grafted methacryloyl chitosan.

[0031] In some embodiments, the temperature of the heating reaction is 30-40°C, and the heating reaction time is 3-4 hours; the temperature of the coupling reaction is 25-40°C, and the coupling reaction time is 24-36 hours.

[0032] Specifically, in step S1, the preparation process of arginine grafted methacryloyl chitosan is as follows: chitosan, acetic acid and PBS buffer are dissolved at a mass ratio of 0.002-0.01:1 at 25°C for 60-90 minutes; methacrylic anhydride and chitosan are added to the solution at a mass ratio of 2-4:1, reacted at 30-40°C for 3 hours, dialyzed and freeze-dried to obtain methacryloyl chitosan; the obtained methacryloyl chitosan is mixed with PBS The buffer solution is dissolved at a mass ratio of 0.0025-0.01:1 at 30-40°C for 30-90 minutes; arginine, EDC, NHS and the prepared solution are added to the solution at a mass ratio of 0.01-0.05:0.01-0.05:0.005-0.025:1, and the mixture is reacted at 25-40°C for 24 hours. After dialysis and freeze-drying, arginine-grafted methacryloyl chitosan (arginine-methacryloyl chitosan) is obtained.

[0033] In the present application, the purity of methacrylic anhydride is 84-90wt%; the purity of gelatin is 90-99%; the purity of arginine is 90-99%; the purity of gallic acid is 90-99%; the purity of chitosan is 90-99%; and the purity of photoinitiator I2959 is 90-99%.

[0034] In some embodiments, the photoinitiator includes photoinitiator 12959.

[0035] Specifically, the steps of photo-crosslinking are as follows: disperse the photoinitiator I2959 in ultrapure water, ultrasonicate at 40-50°C for 30-60min, add zinc-lithium laponite, gallic acid-methacrylylated gelatin and arginine-methacrylylated chitosan and dissolve them in the dark to obtain a mixed solution, load the mixed solution into a 1ml syringe, and photo-crosslink for 60-90s under a 365nm ultraviolet lamp to obtain an antibacterial and antioxidant composite hydrogel; wherein the crosslinking distance under the ultraviolet lamp is 5-10cm.

[0036] The present application provides an application of an antibacterial and antioxidant composite hydrogel in the preparation of a medical wound repair material.

[0037] The present solution is further described below through specific embodiments.

[0038] Example 1 A method for preparing an antibacterial and antioxidant composite hydrogel comprises the following steps: S1. Add 20 mg / mL of laponite to water and stir to swell for 30 minutes, then add zinc nitrate and stir for 20 hours to load the drug. After loading, centrifuge at 6000 r / min for 10 minutes to obtain a solid. Wash the solid several times with water 5 times the volume of the centrifuged material, and then freeze-dry to obtain laponite loaded with zinc ions; dissolve gelatin and PBS buffer at a mass ratio of 0.02:1 at 60°C for 30 minutes; add methacrylic anhydride and the prepared solution at a volume ratio of 0.2:1 to the solution, react at 50°C for 3 hours, dialyze and freeze-dry to obtain methacrylic gelatin; dissolve the obtained methacrylic gelatin and PBS buffer at a mass ratio of 0.02:1 at 50°C for 90 minutes; add gallic acid, EDC, NHS and the prepared solution at a mass ratio of 0.05: The mass ratio of 0.05:0.005:1 was added to the solution, reacted at 40°C for 24 hours, and after dialysis and freeze-drying, gallic acid grafted methacryloyl gelatin (gallic acid-methacryloyl gelatin) was obtained; chitosan, acetic acid and PBS buffer were dissolved at a mass ratio of 0.01:1 at 25°C for 60 minutes; methacrylic anhydride and chitosan were added to the solution at a mass ratio of 2:1, reacted at 30°C for 3 hours, dialyzed and freeze-dried to obtain methacryloyl chitosan; the obtained methacryloyl chitosan was dissolved with PBS buffer at a mass ratio of 0.01:1 at 40°C for 30 minutes; arginine, EDC, NHS and the prepared solution were added to the solution at a mass ratio of 0.01:0.01:0.005:1, reacted at 25°C for 24 hours, dialyzed and freeze-dried to obtain arginine grafted methacryloyl chitosan (arginine-methacryloyl chitosan); S2. Weigh 0.3g of gallic acid-methacryloyl gelatin, 0.01g of arginine-methacryloyl chitosan, 0.005g of I2959 photoinitiator, and 0.001g of zinc-lithium laponite composite, add them into 1ml of ultrapure water, stir and dissolve at 50℃ for 1h, and photocrosslink the dissolved mixed solution under a 365nm ultraviolet lamp at a distance of 10cm from the light source to obtain an antibacterial and antioxidant composite hydrogel.

[0039] Example 2 A method for preparing an antibacterial and antioxidant composite hydrogel, the other contents of which are the same as those of Example 1, except that in step S2, 0.003 g of zinc-hectorite is added.

[0040] Comparative Example 1 A method for preparing an antibacterial and antioxidant composite hydrogel, the other contents of which are the same as those of Example 1, except that in step S2, zinc-hectorite is not added.

[0041] Comparative Example 2 A method for preparing an antibacterial and antioxidant composite hydrogel, the other contents of which are the same as those of Example 1, except that in step S2, 0.005 g of zinc-hectorite is added.

[0042] Test and Evaluation 1. In vitro cytotoxicity test: First, sterilize the prepared hydrogels of Example 1, Example 2, Comparative Example 1 and Comparative Example 2, and soak them in complete culture medium for 24 hours at a concentration of 0.2 g / mL, and then inoculate fibroblasts in a 96-well plate at a density of 5000 cells / well. After the well plate was cultured in a 37°C incubator for 24 hours, the culture medium was aspirated, and the culture medium soaked in the hydrogel was transferred to a 96-well plate and continued to be cultured in the incubator. After 24 hours, the culture medium was discarded, and each well was washed twice with PBS buffer, and a mixture containing MTT (thiazole blue) and culture medium was added to each well in the dark. The mixing ratio of MTT and culture medium was 1:9. After incubation at 37°C for 4 hours, the supernatant was carefully aspirated, and 200 μL of dimethyl sulfoxide (DMSO) was added to each well to dissolve the blue-purple crystals at the bottom of the well plate, and the absorbance was detected at 490 nm with an enzyme marker. Among them, the culture medium was the negative control group, and the culture medium mixture containing 10% phenol was the positive control group.

[0043] The results are as follows Figure 1 As shown, it can be seen that the cell survival rates of Example 1, Example 2 and Comparative Example 1 are 90.96%, 76.62% and 99.86% respectively, and the material toxicity level is Level 1; the cell survival rate of Comparative Example 2 is 45.23%, and the material toxicity level is Level 3, which is moderately toxic.

[0044] 2. Blood compatibility test: Anticoagulated blood was diluted with physiological saline at a dilution ratio of 4:5. The hydrogels prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were respectively immersed in physiological saline, and placed in a water bath at 37°C for half an hour. Then, the diluted blood sample (0.2 mL diluted blood sample / 10 mL physiological saline) was added, and then incubated in a water bath at 37°C for 1 hour. Centrifuged for 5 minutes, the supernatant was taken and the absorbance was measured at 545 nm by a UV spectrophotometer. Ultrapure water was used as the positive control group, and physiological saline was used as the negative control group. The results are shown in Table 1.

[0045] Table 1 Hemolysis test results of different gel materials project Example 1 Example 2 Comparative Example 1 Comparative Example 2 Hemolysis rate / % 2.34 1.56 2.68 3.16 Results (hemolysis rate <5%, safe) Safety Safety Safety Safety 3. Antibacterial test: The test characterizes the antibacterial properties of the material by diluting the bacterial solution and then counting the number of colonies through the coating plate method.

[0046] Bactericidal rate% = (number of CFU in the control group - number of CFU in the experimental group) / (number of CFU in the control group) × 100% Detection bacteria: methicillin-resistant Staphylococcus aureus (ATCC 43300), Escherichia coli (ATCC25922).

[0047] The hydrogels prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 with a thickness of 2 mm were sterilized and added to the test tubes containing 1×107CFU / mL of Escherichia coli and methicillin-resistant Staphylococcus aureus, mixed in a 37°C shaker for 6 hours, then diluted 500 times with phosphate buffer (PBS, pH=7.4), 100 μL of the dilution was applied to the agar plate, placed in a 37°C incubator for 24 hours, the results were observed and the number of colonies was counted. A blank control group was also set up, and the test tubes containing 1×107CFU / mL of Escherichia coli and Staphylococcus aureus were mixed in a 37°C shaker for 6 hours, then diluted 500 times with phosphate buffer (PBS, pH=7.4), 100 μL of the dilution was applied to the agar plate, placed in a 37°C incubator for 24 hours, the results were observed and the number of colonies was counted. The sterilization rate is summarized as shown in Table 2.

[0048] Table 2 Sterilization rate of different gel materials

[0049] 4. Antioxidant experiment: The antioxidant capacity of the hydrogel was determined by testing its ability to scavenge DPPH. In short, 20 mg of freeze-dried hydrogel was soaked in 2 mL of 100 μM DPPH methanol solution and reacted at 37°C for 1 h. The supernatant was taken and the absorbance was measured at 517 nm. DPPH methanol solution was used as a blank control. The results are shown in Figure 2. Figure 2 As shown in Table 3.

[0050] Table 3 Antioxidant properties of different gel materials

[0051] In summary, compared with the prior art, the beneficial effects of the present invention include: 1. The raw materials selected by the present invention have good biocompatibility, wide sources and low prices.

[0052] 2. The composite hydrogel prepared by the present invention has good antibacterial properties, can effectively kill MRSA, and reduce the use of antibiotics.

[0053] 3. The hydrogel prepared by the present invention has good antioxidant properties, can remove ROS, reduce damage to cells, and remove excess ROS in diabetic wounds to promote wound healing.

[0054] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An antibacterial and antioxidant composite hydrogel, It is characterized in that The hydrogel is a hydrogel formed by interpenetrating and cross-linking of zinc ion-loaded laponite, gallic acid-grafted methacryloyl gelatin, and arginine-grafted methacryloyl chitosan.

2. A method for preparing the antibacterial and antioxidant composite hydrogel according to claim 1, It is characterized in that The following steps are involved: S1. Using laponite and zinc nitrate as raw materials, a loading reaction is carried out, and after centrifugation, laponite loaded with zinc ions is obtained; using methacrylic anhydride and gallic acid as raw materials, gelatin is modified to obtain gallic acid-grafted methacrylylated gelatin; using methacrylic anhydride and arginine as raw materials, chitosan is modified to obtain arginine-grafted methacrylylated chitosan; S2. Add the zinc ion-loaded laponite, gallic acid-grafted methacryloyl gelatin, and arginine-grafted methacryloyl chitosan into the dispersion of the photoinitiator in a dark environment, stir evenly, and then perform a cross-linking reaction under ultraviolet light to obtain the antibacterial and antioxidant composite hydrogel.

3. The method for preparing the antibacterial and antioxidant composite hydrogel according to claim 2, It is characterized in that The mass ratio of the zinc ion-loaded laponite, the gallic acid-grafted methacryloyl gelatin, and the arginine-grafted methacryloyl chitosan is (0.1-0.5): (0.2-2): (10-30).

4. The method for preparing the antibacterial and antioxidant composite hydrogel according to claim 2, It is characterized in that In step S1, the preparation process of zinc ion-loaded hectorite is as follows: adding hectorite to water and stirring to swell, then adding zinc nitrate and stirring to carry out loading reaction, and then centrifuging, washing, and drying to obtain the zinc ion-loaded hectorite.

5. The method for preparing the antibacterial and antioxidant composite hydrogel according to claim 2, It is characterized in that In step S1, the preparation process of gallic acid grafted methacryloyl gelatin is as follows: a PBS solution of gelatin is mixed with methacrylic anhydride, heated for reaction, dialyzed, and freeze-dried to obtain methacryloyl gelatin; gallic acid, EDC, and NHS are added to the PBS solution of methacryloyl gelatin to carry out a coupling reaction, dialyzed, and freeze-dried to obtain the gallic acid grafted methacryloyl gelatin.

6. The method for preparing the antibacterial and antioxidant composite hydrogel according to claim 5, It is characterized in that The temperature of the heating reaction is 50-55°C, and the time of the heating reaction is 3-5h; the temperature of the coupling reaction is 25-40°C, and the time of the coupling reaction is 24-36h.

7. The method for preparing the antibacterial and antioxidant composite hydrogel according to claim 2, It is characterized in that In step S1, the preparation process of arginine grafted methacrylylated chitosan is as follows: chitosan, acetic acid and PBS are mixed and stirred to obtain a chitosan solution; methacrylic anhydride is added to the chitosan solution, heated for reaction, dialyzed and freeze-dried to obtain methacrylylated chitosan; arginine, EDC and NHS are added to the PBS solution of methacrylylated chitosan to carry out coupling reaction, dialyzed and freeze-dried to obtain the arginine grafted methacrylylated chitosan.

8. The method for preparing the antibacterial and antioxidant composite hydrogel according to claim 7, It is characterized in that The temperature of the heating reaction is 30-40°C, and the time of the heating reaction is 3-4h; the temperature of the coupling reaction is 25-40°C, and the time of the coupling reaction is 24-36h.

9. The method for preparing the antibacterial and antioxidant composite hydrogel according to claim 2, It is characterized in that The photoinitiator includes photoinitiator I2959.

10. Use of the antibacterial and antioxidant composite hydrogel obtained by the preparation method according to any one of claims 2 to 9 in the preparation of medical wound repair materials.

Citation Information

Cited By

  • Multifunctional photoresponse hydrogel as well as raw materials, preparation method and application thereof

    CN120289674A

  • Multifunctional light-responsive hydrogel, raw material thereof, preparation method and application thereof

    CN120289674B

  • Temperature-responsive intelligent adhesion gelatin-based conductive hydrogel as well as preparation method and application thereof

    CN122587241A